Persepsi Masyarakat Kampung Kranggan Wetan Kota Bekasi terhadap Upacara Pernikahan Penghayat Kepercayaan Aliran Kebatinan Perjalanan - Deny Mardi N; Vicky Verry Angga (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Marriage is a legal relationship between two people recognized by the community based on applicable rules, and its form varies according to each culture. This research focuses on the perceptions of the people of Kranggan Wetan Village, Bekasi City, towards the wedding ceremony of the Believers of Aliran Kebatinan Perjalanan. The purpose is to describe the wedding ceremony process, understand the community's perception, and identify factors that influence the perception. This research uses descriptive method with qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation, then analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. To maintain data validity, source triangulation techniques were used. The result of the research shows that the wedding ceremony process of Penghayat Kepercayaan Aliran Kebatinan Perjalanan is generally similar to the wedding in general. The community's perception of this ceremony is positive as long as it does not conflict with the prevailing norms and rules. Factors that influence people's perception consist of internal factors such as personal experience and knowledge, and external factors such as social and cultural environment. This research provides a new understanding of the diversity of marriage practices in society.